2002
DOI: 10.1089/088282402317340215
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Interferon-βPromoter During Hepatitis C Virus RNA Replication

Abstract: In this study we examined the impact of hepatitis C virus (HCV) RNA replication on the innate antiviral response of the host cell. Replication of an HCV subgenomic replicon stimulated the activation of the interferon (IFN)-beta promoter and the production of IFN in human hepatoma cells. Using a variety of functional assays, we found that HCV RNA replication induced the activation and DNA-binding activity of NFkappaB and interferon regulatory factor (IRF)-1. In addition, microscopy experiments revealed a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 36 publications
3
49
1
Order By: Relevance
“…Interestingly, Fredricksen et al 36 has reported that HCV replicon can activate IFN-␤ promoter and IFN-␤ production. 36 Using RT-PCR, we did not see increased IFN-␤ mRNA expression in FCA1 cells (data not shown). There may be differences among different HCV replicon cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Fredricksen et al 36 has reported that HCV replicon can activate IFN-␤ promoter and IFN-␤ production. 36 Using RT-PCR, we did not see increased IFN-␤ mRNA expression in FCA1 cells (data not shown). There may be differences among different HCV replicon cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of stained cells was conducted in the University of Texas Southwestern Medical Center Pathogen Imaging Facility by using a Zeiss Axiovert or Zeiss Pascal LSM confocal microscope and AXIOVISION software. Electrophoretic mobility-shift analysis of NF-B DNA binding activity was conducted on nuclear extracts prepared from cultures of 4 ϫ 10 5 cells as described (4). RNA Analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that the processes of RIG-I signaling and the actions of IRF-3 and NF-B initiate host defenses that limit HCV RNA replication (1,3,4). The single-stranded RNA genome of HCV encodes a 3,010-aa polyprotein that is posttranslationally processed into the mature structural proteins (core, E1 and E2), p7, and the nonstructural (NS) proteins NS2-NS5B (5), of which the NS3-NS5B proteins are sufficient to support viral RNA replication (Fig.…”
mentioning
confidence: 99%
“…The reason for this is not clear, but could be related to a priming effect rendered by a low level of IFN production within the replicon cells, as has been shown in other studies. 17 The gene lists presented by Zhu et al 13 show that, overall, IFN induced a pattern of ISG expression in Huh7 HCV replicon cells that is consistent with the actions of ISGF3. What the investigators may have overlooked is that known STAT3 target genes, such as p21(waf1), myc, pim-1, cyclin D1, and others 5 were not part of this list.…”
mentioning
confidence: 85%
“…22 The involvement of dsRNA and IRF pathways in ISG signaling events that limit HCV RNA replication has also been shown in studies of the HCV replicon system. 10,17,24 Thus, control of HCV infection and replication is likely to involve a spectrum of ISGs whose expression is determined through complex virus-host interactions that regulate IFN-dependent and IFN-independent signaling pathways.…”
mentioning
confidence: 99%